A formação inicial do enfermeiro sob o paradigma ético-humanista: ênfase às relações interpessoais - Ferla, Josiane Bernart da Silva (2010)
This dissertation gives the results of on investigation into the training of nurses and their link with the ethical-humanist paradigm, giving special attention to interpersonal relationships. The research approach was qualitative, descriptive exploratory. The subjects were graduates and teachers from the School of Nursing. Data collection was performed in 2009 by using the techniques of documentary analysis Project of the undergraduate course in Nursing, application of questionnaire to graduates of undergraduate nursing, semi-structured interviews with teachers of the Evangelical University of Paraná. The data collected were subjected to content analysis, which revealed three categories. The first category, Whole / Multidimensionality integrates with the proposed curriculum guidelines, when considering the background of the various dimensions of the relationship between individual and society, within the context of the whole being. The second category, Interdisciplinary / Disciplinarity / Theory-Practice Dichotomy, shows a trajectory of training that permeates the concrete transcendence between the expertise and knowledge to be a nurse. And finally, the third category, Interpersonal Relations / Interpersonal Skills that were considered by subjects as a facilitator of the work process and the development of individual and collective character of the subject in training. The results indicate that both teachers and students perceive the academic still focused on technical and scientific references, but with a real intent of skills training also focused on human relations. This study revealed the influence of ethical and humanistic paradigm proposed by the curriculum guidelines in the process of nursing education and also has reinforced the need for new opportunities unfolding of ideas, to thing again training in nursing to be able to be based pedagogical principles that address whole of being in training and be assisted by health professionals.